Putting farmers’ strategies in the center of agricultural groundwater use in the Vientiane Plain, Laos - Suhardiman, Diana; Pavelic, Paul; Keovilignavong, Oulavanh; Giordano, Mark (Informa UK Limited, 2020)
Groundwater use for agriculture has the potential to improve rural households’ income and reduce poverty, but the linkages are not always straightforward. Taking Laos as a case study, this article illustrates how differential access to water, land, and capital shape farmers’ livelihood strategies in two nearby, yet contrasting villages on the Vientiane Plain. It examines the factors driving farm households’ decisions to invest in groundwater for agriculture. The findings highlight the need to better understand how farmers view groundwater in relation to their farm household characteristics if groundwater is to be successfully used as a means to improve rural livelihoods.